Homoeopathy and Atopic Dermatitis: An Evidence-Based Clinical Case Report (Advancements in Homeopathic Research, 2022)
Atopic dermatitis is a common inflammatory skin disorder characterized by recurrent skin lesions with severe intolerable itching. This disease condition can affect all age groups. Multiple comorbidities are associated with atopic dermatitis-like atopic asthma, allergic rhinitis time mental disorders. There is no permanent recovery of this condition. Still, increasing numbers of innovative and targeted therapies like (corticosteroids, Antihistamines, Immuno-suppressant drugs, antibacterial medicines, light therapy, etc.) are being used to control the disease condition. There is a valuable role of homoeopathy in different skin diseases, including atopic dermatitis. This article illustrates a documented case report of a patient with atopic dermatitis. In this particular case, atopic dermatitis condition is treated by Natrum muriaticum, based on the constitutional totality of the patient. The improvement was documented by SCORAD (scoring atopic dermatitis) and photography evidence during follow up.[1]
Keywords: Atopic dermatitis; Conventional treatment; Homoeopathy; Natrum muriaticum